Proteasomal processing of the viral replicase ORF1 facilitates HEV-induced liver fibrosis - Fei Zhang; Ling-Dong Xu; Shiying Wu; Qirou Wu; Ailian Wang; Shengduo Liu; Qian Zhang; Xinyuan Yu; Bin Wang; Yinghao Pan; Fei Huang; Dante Neculai; et al. (Proceedings of the National Academy of Sciences, 2025)
Chronic infections with hepatitis E virus (HEV), especially those of genotype 3 (G3), frequently lead to liver fibrosis and cirrhosis in patients. However, the causation and mechanism of liver fibrosis triggered by chronic HEV infection remain poorly understood. Here, we found that the viral multiple-domain replicase (ORF1) undergoes unique ubiquitin–proteasomal processing leading to formation of the H EV- D erived S MAD A ctivator (HDSA), a viral polypeptide lacking putative helicase and RNA polymerase domains. The HDSA is stable, non-HSP90-bound, localizes to the nucleus, and is abundant in G3 HEV-infected hepatocytes of various origins. Markedly, the HDSA in hepatocytes potentiates the fibrogenic TGF-β/SMAD pathway by forming compact complexes with SMAD3 to facilitate its promoter binding and coactivator recruitment, leading to significant fibrosis in HEV-susceptible gerbils. Virus infection–induced liver fibrosis in HEV-susceptible gerbils could be prevented by mutating the residues P989C, A990C, and A991C (PAA-3C) within ORF1, which are required for proteasomal processing. Thus, we have identified a viral protein derived from host proteasomal processing, defined its notable role in liver fibrosis and highlighted the nature of an unanticipated host–HEV interaction that facilitates hepatitis E pathogenesis.